Clinically significant responses achieved with romidepsin across disease compartments in patients with cutaneous T-cell lymphoma. Issue 10 (3rd October 2015) - Kim, Ellen J.; Kim, Youn H.; Rook, Alain H.; Lerner, Adam; Duvic, Madeleine; Reddy, Sunil; Robak, Tadeusz; Becker, Jürgen C.; Samtsov, Alexey; McCulloch, William; Waksman, Joel; Whittaker, Sean
Abstract : Cutaneous T-cell lymphoma (CTCL) is a rare heterogeneous group of non-Hodgkin lymphomas that arises in the skin but can progress to systemic disease (lymph nodes, blood, viscera). Historically, in clinical trials of CTCL there has been little consistency in how responses were defined in each disease "compartment"; some studies only assessed responses in the skin. The histone deacetylase inhibitor romidepsin is approved by the US Food and Drug Administration for the treatment of CTCL in patients who have received at least one prior systemic therapy. Phase II studies that led to approval used rigorous composite end points that incorporated disease assessments in all compartments. The objective of this analysis was to thoroughly examine the activity of romidepsin within each disease compartment in patients with CTCL. Romidepsin was shown to have clinical activity across disease compartments and is suitable for use in patients with CTCL having skin involvement only, erythroderma, lymphadenopathy and/or blood involvement.